"Weak Is the New Strong": Gendered Meanings of Recovery from Substance Abuse among Male Prisoners Participating in Narcotic Anonymous Meetings. (April 2021) - Gueta, Keren; Gamliel, Sharon; Ronel, Natti
Much of what has been written about prison masculinity has focused on the hypermasculine climate of prisons that rewards aggression and the concealment of vulnerability. However, the findings of more recent studies have indicated a more varied ideal of masculinity in this environment. The present research examined how inmates construct and understand masculinity within the domain of reformatory intervention. Interpretative phenomenological analysis was performed on fourteen transcribed interviews with inmates who participated in Narcotics Anonymous (NA). The results indicated that hypermasculinity ideals hindered the participants' ability to apply the tenets of NA that threatened their masculine identity, such as admitting powerlessness. However, they sought to negotiate these threats by employing three main discursive strategies. First, they affirmed hegemonic masculinity notions by presenting themselves as pragmatic agents, offsetting criticism of their submission to higher authorities, constructing recovery as a masculine act, and othering drug-using men. Second, they reformulated ideas of masculinity by adapting the concept to include feminine notions of caring and admitting vulnerability, in line with their NA experience. Third, they rejected their former ideologies and their current dominant localized sociocultural constructions of hypermasculinity that stigmatized them by noting the superiority of NA as a space of support, egalitarian relationships between inmates, and trust relationships with prison staff. By focusing on the dynamic of stigma, marginalization, and masculinity, the research informs both the theoretical understanding of masculinity and the development of reformatory interventions in prison.